The Impact of Anticipated Social Consequences on Recurring Disability Accommodation Requests - Baldridge,David; Veiga,J. F. (Journal of Management, 2006)
The Americans with Disabilities Act of 1990 (ADA) has not achieved its potential, in part, because those it sought to help have shown a reluctance to request accommodations. Using survey data from 229 hearing-impaired employees and an expert panel, logistic regression confirmed that monetary costs and impositions on others negatively influence the likelihood of requesting recurring accommodations. Furthermore, monetary costs and impositions on others negatively influence the requester's assessments of the social consequences of making such requests. These consequences, in turn, can also negatively influence future disability accommodation requests.
Keywords: Management